Triple correlation for detection of damage-related nonlinearities in composite structures - Klepka, Andrzej; Strączkiewicz, Marcin; Pieczonka, Lukasz; Staszewski, Wieslaw Jerzy; Gelman, Leonid; Aymerich, Francesco; Uhl, Tadeusz (Springer, 2015)
Nonlinear effects in vibration responses are investigated for the undamaged composite plate and the composite plate with a delamination. The analysis is focused on higher harmonic generation in vibration responses for various excitation amplitude levels. This effect is investigated using the triple correlation technique. The dynamics of composite plate was modelled using two-dimensional finite elements and the classical lamination theory. The doubled-node approach was used to model delamination area. Mode shapes and natural frequencies were estimated based on numerical models. Next, the delamination divergence analysis was used to obtain relative displacements for delaminated plies. Experimental modal analysis test was carried out to verify the numerical models. The two strongest vibration modes as well as two vibration modes with the smallest and largest motion level of delaminated plies were selected for nonlinear vibration test. The Fisher criterion was employed to verify the effectiveness and confidence level of the proposed technique. The results show that the method can be used not only to reveal nonlinearities, but also to reliably detect impact damage in composites. These results are confirmed using the statistical analysis.
Keywords: Composites; Damage-related nonlinearities; Impact damage detection; Nonlinear vibration; Higher harmonics generation; Triple correlation